The Event of Art - Lafia, Marc (punctum books, 2020)
"The Event of Art presents, in fifty-two modular chapters and over eight hundred pages and images, the works of artist Marc Lafia. The book interweaves essays, notes, photographic archives, and a host of exhibitions wherein Lafia traverses his wide body of work and examines how his early strategies of cultural reading of photography and film, of interface, network culture, and social media, transform into an investigation of materiality itself. If his interest was once the way media becomes the message, his interest later becomes the realm of the sensible and the sensate in themselves. Here he presents art as the medium itself, giving us wide permission to explore and examine our deepest feelings and senses, our world and its becoming. The book is introduced by two essays. The first is by curator and art dealer Mathieu Borysevicz, where he recounts meeting Lafia at his first artist residency, and the many projects they would go on to do together. He introduces Lafia's interest in recording as it becomes digital and computational where ""recording is not only memory, and a data structure, but a permutational instrument and ever-changing horizon of iterations." The other introductory essay is by critic Daniel Coffeen, who writes, ""while Lafia may not have a traditional medium - there is no such thing anymore - he does in fact have one consistent medium: imaging making itself, its apparati of creation, consumption, and circulation. In fact Lafia's medium is the discourse of art - what it is, how it comes to be, how we experience it." The Event of Art presents the work of art as a complex material and societal event. The event is multiple, a continual becoming of perception, being, materiality, participation, a coming to the senses and the making, shaping and opening to them, not only of one's self, but the world becoming."